The Linguistic Duality Debate in English Canada in 2019, 1969, and 1929 - Talbot, Robert (Minorités linguistiques et société / Linguistic Minorities and Society, 2021)
Changes to the political landscape have revived the debate over linguistic duality. That debate, however, is not altogether new. Many of the arguments being made in 2019, upon the fiftieth anniversary of the Official Languages Act, were not unlike those of 1969, when Canada adopted the Act, or even 1929, when government took modest measures to recognize English and French at the post office.In 1929, 1969 and 2019, some believed that pan-Canadian recognition of linguistic duality would serve national unity. Others, however, wondered whether it was compatible with the ethnocultural diversity of the country, or asserted that federal bilingualism in their province was not justified, citing populist, demographic or identity-based arguments. The debate—90 years ago, 50 years ago, or even today—has often given rise to fear and misunderstanding; however, it has also benefited from the persistence of moderates from both of Canada’s official language communities.